CHARACTERISTICS AND CLINICAL OUTCOMES OF ADULT DENGUE PATIENTS WITH WARNING SIGNS: A CROSS-SECTIONAL STUDY AT THE HOSPITAL FOR TROPICAL DISEASES IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the proportion of dengue patients with warning signs who progressed to severe dengue and to describe the characteristics of warning signs, including their predictive values.Methods: A cross-sectional descriptive study was conducted among 400 hospitalized dengue patients aged 16 years or older with warning signs at the Hospital for Tropical Diseases from May 2020 to October 2021. Warning signs were described according to severe progression status. Exploratory analyses included the predictive values of individual warning signs.Results: Severe dengue progression occurred in 8.75% of patients, with shock due to plasma leakage being the most common severe manifestation. Most warning signs had low positive predictive values, whereas their negative predictive values were high. The number of warning signs showed good discrimination for severe progression, with an AUC of 0.883 (95% CI: 0.847-0.913). Hepatomegaly, fluid accumulation, and rising hematocrit with rapid platelet decrease were independently associated with severe progression.Conclusion: The proportion of severe progression among adult dengue patients with warning signs was comparable to that reported in other studies. The number of warning signs may have potential value in predicting severe progression. Further validation in broader populations is needed.
Keywords: Dengue fever, severe dengue, warning signs, aged 16 years or older, risk stratification